Silicon reduces impact of plant nitrogen in promoting stalk borer (Eldana saccharina) but not sugarcane thrips (Fulmekiola serrata) infestations in sugarcane - Keeping, Malcolm G.; Miles, Neil; Sewpersad, Chandini (Frontiers in Plant Science, 2014)
The stalk borer Eldana saccharina Walker (Lepidoptera: Pyralidae) is a major limiting factor in South African sugarcane production, while yield is also reduced by sugarcane thrips Fulmekiola serrata Kobus (Thysanoptera: Thripidae). Borer management options include appropriate nitrogen (N) and enhanced silicon (Si) nutrition; the effect of N on sugarcane thrips is unknown. We tested the effects of these nutrients, in combination with resistant (N33) and susceptible (N27) sugarcane cultivars, on E. saccharina and F. serrata infestation. Two pot trials with three levels of N (60, 120 and 180 kg ha-1) and two levels each of calcium silicate and dolomitic lime (5 t ha-1, 10 t ha-1) were naturally infested with thrips, then artificially water stressed and infested with borer. Higher N levels increased borer survival and stalk damage, while Si reduced these compared with controls. Silicon significantly reduced stalk damage in N27 but not in N33; hence, Si provided relatively greater protection for susceptible cultivars than for resistant ones. High N treatments were associated with greater thrips numbers, while Si treatments did not significantly influence thrips infestation. The reduction in borer survival and stalk damage by Si application at all N rates indicates that under field conditions, the opportunity exists for optimising sugarcane yields through maintaining adequate N nutrition, while reducing populations of E. saccharina using integrated pest management (IPM) tactics that include improved Si nutrition of the crop and reduced plant water stress. Improved management of N nutrition may also provide an option for thrips IPM. The contrasting effects of Si on stalk borer and thrips indicate that Si-mediated resistance to insect herbivores in sugarcane has mechanical and biochemical components that are well developed in the stalk tissues targeted by E. saccharina but poorly developed in the young leaf spindles where F. serrata occurs.